Outsourcing and offshoring in the 21st century a socio-economic perspective - Kehal, Harbhajan S. 1942-; Singh, Varinder P. 1974- (Idea Group, 2006)
"This book discusses the economic impacts of outsourcing and off shoring to the developing countries and developed countries and the short term and long term implications"--Provided by publisher.